Presumtion of political terms and concepts konvectionalism in reseaching history of communist regime in Lithuania - Bauža, Česlovas (Genocidas ir rezistencija, 2001)
Terminology is best understood by philologists. Lawyers, philosophers, and other experts in their fields may have a better understanding of the concepts. This is probably where the synthesis between terms and concepts lies. The present presentation deals with various concepts and terms related to the Soviet era.
Keywords: Soviet regime; communist party; concepts